Strategi Pemasaran Digital untuk Meningkatkan Daya Saing Petani Kentang di Banyumas: Analisis Pemanfaatan Media Sosial dan E-Commerce - Suwali, Suwali; Maulia, Regizki Maulia (Jurnal Bisnis dan Kewirausahaan, 2025)
The adoption of digital marketing among potato farmers in Banyumas has significantly influenced their market competitiveness. This study explores how social media and e-commerce platforms enhance market access, customer engagement, and business sustainability. Using Diffusion of Innovation Theory, the research examines factors affecting farmers' adoption of digital marketing, including digital literacy, financial constraints, external support, and customer trust. A qualitative approach was employed, involving in-depth interviews with six selected informants. The findings reveal that farmers who actively utilize digital platforms experience increased visibility and sales. However, challenges such as technical expertise, logistics, and seasonal demand fluctuations hinder optimal implementation. Government and private-sector support play a crucial role in fostering digital adoption through training programs and financial assistance. The study highlights the need for structured interventions to bridge the digital divide among farmers. Additionally, strengthening digital literacy and enhancing collaboration among stakeholders can further accelerate the adoption of digital marketing in agriculture. Future research should explore broader agricultural sectors and examine policy interventions that facilitate digital transformation. This study contributes to the growing body of knowledge on digital marketing in rural economies and provides practical insights for farmers, policymakers, and agricultural organizations.